2021
DOI: 10.1021/acscatal.1c00218
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Infrared Spectroscopy for the Analysis of Gas-processing Metalloenzymes

Abstract: Earth-abundant transition metals, such as iron, nickel, copper, molybdenum, and vanadium, have been identified as essential constituents of the cellular gas metabolism in all kingdoms of life. Associated with biological macromolecules, gas-processing metalloenzymes (GPMs) are formed that catalyze a variety of redox reactions. This includes the reduction of O2 to water by cytochrome c oxidase (“complex IV”), the reduction of N2 to NH3 by nitrogenase, as well as the reversible reduction of protons to H2 by hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 155 publications
2
57
0
Order By: Relevance
“…Of course, this mechanism cannot apply in the case of the enzyme from C. reinhardtii, but we show that reactivation can actually occur after the H-cluster in the H trans state is one-electron reduced; the final product, H ox , is still isoelectronic with H trans because of either the potentiometric reoxidation or the auto-oxidation of the reduced states of the H-cluster in the absence of H 2 (as reported before by Stripp et al ,, ). We consider likely that this mechanism also applies in the case ofD.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Of course, this mechanism cannot apply in the case of the enzyme from C. reinhardtii, but we show that reactivation can actually occur after the H-cluster in the H trans state is one-electron reduced; the final product, H ox , is still isoelectronic with H trans because of either the potentiometric reoxidation or the auto-oxidation of the reduced states of the H-cluster in the absence of H 2 (as reported before by Stripp et al ,, ). We consider likely that this mechanism also applies in the case ofD.…”
Section: Discussionsupporting
confidence: 75%
“…suggested that, at least in the case of the enzyme from D. desulfuricans, the reactivation of H trans is triggered by the reduction of an accessory cluster, which induces H 2 S release from the distal Fe by an anti-cooperative, long distance interaction with the H-cluster. Of course this mechanism cannot apply in the case of the enzyme from C. reinhardtii, but we show that reactivation can actually occur after the H trans state is one-electron reduced; the final product is still isoelectronic with H trans , because of either the potentiometric re-oxidation or the auto-oxidation of the reduced states of the H-cluster in the absence of H 2 (as reported before by Stripp et al 14,74,75 ). We consider likely that this simple mechanism also applies in the case of D. desulfuricans hydrogenase.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our setup ( Senger et al, 2018 ) allowed the rapid exchange of the atmosphere over the protein film with 40% O 2 , triggering the oxidation of Rs C c O. N 2 was used as a carrier over the whole experiment. Every difference spectrum is the result of a different number of co-additions of pre-trigger and post-trigger absolute spectra that maximized SNR ( Stripp, 2021 ), ranging from a minimum of 20 scans to a maximum of 500.…”
Section: Methodsmentioning
confidence: 99%